Government policy and private sector development in post-conflict states: Growing Cambodia's rice production and export industries. (June 2017) - Turner, Mark; Korm, Ribaun; Veara, Kim
This article deals with the rehabilitation of economies in post-conflict states, paying particular attention to the role played by the state in this process. Using the example of Cambodia and its policies on rice production and export, the article shows the prominent role that may be played by the state in prioritised areas of economic development where there has been market failure. In the Cambodian case, the government targeted rice production and export as these had great potential for promoting the major aims of national development policy – economic growth and poverty alleviation. Using a whole-of-government approach and a combination of direct involvement and the creation of an enabling environment, the government appears to have contributed to vastly increased rice production and export.